HAWC and Fermi-LAT Detection of Extended Emission from the Unidentified Source 2HWC J2006+341 - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Araya, M.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; et al. (Astrophysical Journal Letters, 2020)
The discovery of the TeV point source 2HWC J2006+341 was reported in the second HAWC gamma-ray catalog. We present a follow-up study of this source here. The TeV emission is best described by an extended source with a soft spectrum. At GeV energies, an extended source is significantly detected in Fermi-LAT data. The matching locations, sizes, and spectra suggest that both gamma-ray detections correspond to the same source. Different scenarios for the origin of the emission are considered and we rule out an association to the pulsar PSR J2004 +3429 due to extreme energetics required, if located at a distance of 10.8 kpc.
CRIS-Team Scopus Importer:2020-11-20